1,3-Benzothiazole–oxalic acid (2/1) - Abdalsalam, Ashraf Ahmad Ali (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, C(7)H(5)NS·0.5C(2)H(2)O(4), contains one benzothiazole molecule and half an oxalic acid molecule, the complete molecule being generated by inversion symmetry. The benzothiazole molecule is essentially planar, with a maximum deviation of 0.007 (1) Å. In the crystal, the benzothiazole molecules interact with the oxalic acid molecules via O—H⋯N and C—H⋯O hydrogen bonds generating R (2) (2)(8) (× 2) and R (4) (4)(10) motifs, thereby forming supramolecular ribbons along [101].